Kedudukan Badan Permusyawaratan Desa (BPD) Sebagai Lembaga Pengawas Terhadap Kinerja Kepala Desa di Dalam Pemerintahan Desa - I Gusti Made Bayu Nugraha; I Gusti Bagus Suryawan; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2021)
Local government is an efficient and effective form of government, because the central government cannot handle all the complex problems of the state. The problem raised in this study is about the authority of the village consultative body as a supervisory agency for the performance of the village head. The purposes of this study are to examine the position of the village consultative body in the village government and the implementation of BPD supervision on the performance of the village head in the village government. The method used is a normative legal research method with a case approach. The technique of data collection is done by literature study. The sources of legal materials used are primary, secondary and tertiary sources of legal materials which are then analyzed systematically. The results of the study indicate that the authority of the village consultative body is to hold meetings with the community to collect their wishes, channel the wishes of the community to the village government both orally and in writing, present the draft Perdes under its authority, monitor and evaluate the performance of the village head, request information on the administration of village governance to the village head. village government, express opinions on the implementation of village governance, carry out village development, promote village communities and empower village communities